Fakta Sejarah Pada Novel “Gadis Kretek” Karya Ratih Kumala (Kajian New Historicism) - Syafitri, Hanun Dinah; Afdholy, Nadya; Purnomo, Antonius Rahmad Pujo (Universitas Muhammadiyah Kotabumi, 2025)
This research aims to analyze the novel Gadis Kretek by Ratih Kumala using the New Historicism approach. This approach examines how literary works not only reflect but also participate in the construction of social, cultural, and political realities within specific historical context. The novel was selected due to its rich historical, social, and cultural narrative, particularly related to Indonesia’s clove cigarette (kretek) industry from the colonial period to the New Order era. The research uses a qualitative descriptive mthod with reading-note techniques and interpretive analysis of excerpts that depict representation of history, society, economy, education, and culture. The findings reveal that Gadis Kretek represents Javanese society in various dimensions, including social inequality, patriarchal systems, colonial repression, and the role of local culture in shaping national identity. The novel illustrates how power operates through historical and economic discourse. Therefore, Gadis Kretek stands as a culturally rich text that is highly relevant for analysis through the lens of New Historicism.